The virtual research community: a new arena of scientific communication - DOI: 10.3395/reciis.v1i2.92en - Rejane Machado; Maria Elisa Andries Reis (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2007)
Over the last 30 years, the introduction of new communications techniques and information has generated a historical rupture, a paradigm break, resulting from innovative technological transformations. In this context, the virtual research community appears as a new cognitive social grouping for collective, interactive and interdisciplinary scientific practices, establishing selective patterns of relationships in the academy. Those new patterns are substituting the contact territory boundary, giving larger reach and speed to research, starting with their authors' interaction, independent of time and space. It is in this virtual arena that researchers feel changes in experiences, sharing of information, and mutual collaboration in research. The present study approaches the transformations of the scientific communication and points out the virtual communities' role in the current social context.